Ch. 54-Protecting Game on Lake Washington, §§ 1-3, in Session Laws of the State of Washington Eleventh Session (1909). - (:unkn) unknown (My University, 1909)
That it shall be unlawful to fire any gun or to kill, shoot, entrap, ensnare, maim, or destroy any wild birds at any season of the year upon the waters of Lake Washington, or within one mile of its shores, and any person who shall kill, shoot, entrap, ensnare, destroy, or maim any wild birds at any season of the year upon the waters of Lake Washington, or within one mile of the shores of said lake, shall be guilty of a misdemeanor, and, upon conviction thereof, shall be punished as hereinafter provided.
Keywords: HUNTING REGULATION